A 3D printing method of a gradient aluminum-carbon-based ceramic composite material
Patent Information
- Application Number
- CN202611115512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对现有技术中的上述不足,本发明提供一种梯度铝-碳基陶瓷复合材料的3D打印制备方法,通过动态调控碳基陶瓷粉末与造孔剂的比例,实现三维连续梯度预制体的制备,并结合真空压力浸渗工艺,有效解决复杂结构成型、熔渗不完全与界面结合的难题
[0013]本发明提供的一种梯度铝-碳基陶瓷复合材料的3D打印制备方法,通过动态调控碳基陶瓷粉末与造孔剂的比例,实现了3D打印产品在Z轴方向上的连续或阶梯式梯度结构,并通过控制孔隙率(20%~50%)结合真空压力浸渗工艺,有效解决了复杂结构成型、熔渗不完全与界面结合的难题。该方法具有工艺可控性强、适用于复杂结构、界面结合优良等优点,适于工业化推广应用。
Abstract
Description
Technical Field
[0001] This invention relates to the field of 3D printing technology, and more specifically, to a 3D printing preparation method for a gradient aluminum-carbon-based ceramic composite material. Background Technology
[0002] Aluminum-carbon-based ceramic (such as Al / SiC) composites have broad application prospects in aerospace, electronic packaging, and automotive lightweighting due to their high specific strength, low coefficient of thermal expansion, and good thermal conductivity. Traditional aluminum-carbon-based ceramic composites typically employ uniform particle or fiber reinforcement designs, but this uniform structure struggles to simultaneously meet the material's performance requirements in areas such as wear resistance, thermal shock resistance, and interfacial bonding strength. In recent years, gradient structure design has been introduced into the field of aluminum-carbon-based ceramic composites. By controlling the distribution gradient of the reinforcing phase (carbon-based ceramic) (such as particle size, volume fraction, and alignment), spatially differentiated optimization of material properties can be achieved. For example, the surface strengthening layer requires high volume fraction carbon-based ceramic particles to improve surface hardness and wear resistance; the transition layer requires medium-particle carbon-based ceramic to form a gradient interface with the aluminum matrix to alleviate thermal stress concentration; and the core toughening layer requires low volume fraction coarse-particle carbon-based ceramic or a porous structure to improve overall impact resistance.
[0003] Despite the significant advantages of gradient aluminum-carbon-based ceramic composites, their fabrication technology still faces challenges. Traditional methods (such as hot pressing and powder metallurgy) struggle to achieve continuous and controllable gradient changes, easily leading to weak interfacial bonding and abrupt performance changes. Carbon-based ceramics exhibit poor wettability with the aluminum matrix, and traditional processes struggle to eliminate interfacial defects (such as porosity and reaction layers). For example, gradient materials prepared by stirred casting exhibit a brittle Al4C3 phase at the interface, causing material failure at high temperatures. Furthermore, while technologies such as chemical vapor deposition (CVD) and laser cladding can achieve gradient structures, they involve large equipment investments and low production efficiency, making them unsuitable for industrial-scale applications. In recent years, the rise of 3D printing technology has brought new opportunities to the preparation of composite materials, greatly improving design freedom and manufacturing efficiency, making it possible to manufacture parts that were previously difficult to manufacture due to their complex shapes. After completing the 3D printing of carbon-based ceramic green bodies, the aluminizing process also shows unique advantages, allowing molten aluminum to fully fill the pores of the carbon-based ceramic green body, forming a continuous aluminum phase, thereby improving the density and integrity of the composite material. However, how to achieve the gradient of 3D-printed carbon-based ceramic green bodies and solve the problems of complex structure forming, incomplete melting and infiltration, and interface bonding remain the current technical bottlenecks in the industry. Summary of the Invention
[0004] To address the aforementioned shortcomings in existing technologies, this invention provides a 3D printing method for preparing gradient aluminum-carbon-based ceramic composite materials. By dynamically controlling the ratio of carbon-based ceramic powder to pore-forming agent, a three-dimensional continuous gradient preform is prepared. Combined with a vacuum pressure infiltration process, this method effectively solves the problems of complex structure forming, incomplete melting and infiltration, and interface bonding.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A 3D printing method for preparing gradient aluminum-carbon based ceramic composite materials includes the following steps: S1, Pretreatment: Pre-oxidation treatment of carbon-based ceramic powder; S2, Gradient ratio powder mixing: The pre-oxidized carbon-based ceramic powder is mixed with the pore-forming agent according to the preset gradient ratio to obtain mixed powders with different ratios. S3, Powder Spreading Printing: Using binder jet 3D printing technology, different gradient ratios of mixed powders are used to spread and print the product in layers according to the requirements of different parts of the product in the Z-axis direction, so as to make a 3D printed product blank with a gradient structure. S4, Post-processing: The 3D printed product green body is sequentially cured, degreased and sintered to obtain a carbon-based ceramic preform with a gradient pore structure; S5, Aluminizing: The carbon-based ceramic preform is placed in a vacuum pressure infiltration furnace for aluminizing treatment to obtain a gradient aluminum-carbon-based ceramic composite material.
[0006] In some embodiments, in step S2, the mixed powder is divided into a first gradient ratio, a second gradient ratio, and a third gradient ratio according to the performance requirements of different parts of the product along the Z-axis; in step S3, the mixed powder with the first gradient ratio is used in the first to n layers, the mixed powder with the second gradient ratio is used in the (n+1) to m layers, and the mixed powder with the third gradient ratio is used in the (m+1) to z layers, where n, m, and z are positive integers and n... <m<z。
[0007] In some embodiments, in step S2, the carbon-based ceramic powder and the pore-forming agent are placed in different powder feeding troughs of the powder supply system, and the mixing ratio of the carbon-based ceramic powder and the pore-forming agent is controlled by controlling the powder feeding speed of each powder feeding trough; in step S3, the powder falling from each powder feeding trough is mixed in a powder spreading trough, and then spread for printing. The powder supply system is preferably a dual-vibration feeder combined with a screw for precise powder feeding, with an accuracy of ±0.5 vol.
[0008] In some embodiments, the pore-forming agent is polystyrene with an average particle size of 5–20 μm; the carbon-based ceramic powder is carbon-based ceramic powder with an average particle size of 20–50 μm and a purity greater than 99.5%.
[0009] In some embodiments, in step S1, the pre-oxidation treatment is carried out in a muffle furnace at a temperature of 900–1400°C for a holding time of 60–120 min. Pre-oxidation of the carbon-based ceramic powder effectively avoids interfacial reactions between the carbon-based ceramic and the molten aluminum during the subsequent aluminizing process, while also improving the wettability of the carbon-based ceramic particles with the molten aluminum.
[0010] In some embodiments, in step S4, the curing temperature is 120–180°C and the curing time is 60–180 min; the degreasing process is as follows: the temperature is increased to 350–750°C at a heating rate of 1–5°C / min, and held for 1–4 h, with nitrogen or argon in the degreasing atmosphere, so that the binder and pore-forming agent are completely decomposed and discharged; then the temperature is increased to 1000–1200°C at a heating rate of 5–10°C / min, and held for 1–2 h, so that neck connections are formed between carbon-based ceramic particles (neck diameter > 1 μm), and the green compact compressive strength reaches 20–50 MPa.
[0011] In some embodiments, in step S5, the vacuum pressure infiltration furnace is evacuated to 1.5–4.0 MPa, heated to 680–720 °C at a heating rate of 5–10 °C / min, held at that temperature for 5–15 min, and then high-purity nitrogen or argon is introduced at a pressure of 2–5 MPa. The temperature is then maintained for another 30–90 min to allow the molten aluminum to fully infiltrate into the gradient pores of the preform.
[0012] In some embodiments, in step S3, the printing layer thickness is 40–100 μm, the binder saturation is 40%–75%, and the volume fraction of carbon-based ceramic is 20%–50%.
[0013] This invention provides a 3D printing method for gradient aluminum-carbon-based ceramic composite materials. By dynamically controlling the ratio of carbon-based ceramic powder to a pore-forming agent, a continuous or stepped gradient structure in the Z-axis direction is achieved in the 3D printed product. Furthermore, by controlling the porosity (20%–50%) combined with a vacuum pressure infiltration process, the challenges of complex structure forming, incomplete melting and infiltration, and interfacial bonding are effectively solved. This method offers advantages such as strong process controllability, applicability to complex structures, and excellent interfacial bonding, making it suitable for industrial application. Detailed Implementation
[0014] This invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this invention.
[0015] It should be noted that when an element is referred to as being "set on" another element, it can be directly on the other element or there may be an intervening element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or there may be an intervening element. The terms "vertical," "horizontal," "left," "right," "top," "bottom," "end," "top," and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.
[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0017] This invention provides a 3D printing method for preparing gradient aluminum-carbon based ceramic composite materials, comprising the following steps: S1, Pretreatment: The carbon-based ceramic powder is pre-oxidized. Specifically, the carbon-based ceramic powder is placed in a muffle furnace for pre-oxidation at a temperature of 900–1400°C for a holding time of 60–120 min. Preferably, the temperature is 1300°C and the holding time is 60 min. Pre-oxidation of the carbon-based ceramic powder prevents the reaction between the carbon-based ceramic and the molten aluminum during subsequent aluminizing, and also improves the wettability of the carbon-based ceramic particles with the molten aluminum.
[0018] S2, Gradient ratio powder mixing: The pre-oxidized carbon-based ceramic powder and the pore-forming agent are mixed according to the preset gradient ratio; that is, according to the requirements of different parts in the Z-axis direction of the 3D printed product, the carbon-based ceramic powder and the pore-forming agent are mixed in a gradient ratio, that is, the carbon-based ceramic powder and the pore-forming agent are mixed in different ratios to form mixed powders of different proportions.
[0019] S3, Powder Spreading Printing: Utilizing binder jetting 3D printing technology, a powder spreader lays powder according to different gradient ratios to create gradient 3D printed product blanks. Specifically, based on the requirements of different parts of the 3D printed product along the Z-axis, for example, the first gradient ratio of mixed powder is used for layers 1 to n, the second gradient ratio for layers n+1 to m, and the third gradient ratio for layers m+1 to z. During the printing process, the powder spreader lays a layer of powder, and the nozzle sprays a layer of binder along with it. After powder cleaning, the printed product will have different gradient ratios along the Z-axis. For example, dividing the printed product into three gradient ratios along the Z-axis, the volume fraction of carbon-based ceramic powder increases from 10% in the first gradient to 30% in the second gradient, and then to 50% in the third gradient, resulting in different porosities for each gradient and thus different aluminization content for each gradient.
[0020] S4, Post-processing: The gradient 3D printed product preform is cured, degreased, and sintered to obtain a gradient 3D printed product preform. S5, Aluminizing: The 3D printed product preform is placed in a vacuum pressure infiltration furnace for aluminizing to obtain a gradient aluminum-carbon-based ceramic composite material.
[0021] In one embodiment, in step S2, carbon-based ceramic powder and pore-forming agent are mixed in a certain gradient ratio according to the requirements of different parts of the product in the Z-axis direction to obtain mixed powder with a first gradient ratio, mixed powder with a second gradient ratio, and mixed powder with a third gradient ratio. In step S3, during the powder spreading of layers 1 to n, the powder supply system delivers mixed powder of a first gradient ratio to the powder spreader; during the powder spreading of layers n+1 to m, the powder supply system delivers mixed powder of a second gradient ratio to the powder spreader; and during the powder spreading of layers m+1 to z, the powder supply system delivers mixed powder of a third gradient ratio to the powder spreader. Specifically, during the powder spreading of layers 1 to n, the powder supply system supplies mixed powder of a first gradient ratio to the lower powder trough of the powder spreader. After the powder spreading of layers 1 to n is completed, the remaining mixed powder of the first gradient ratio in the lower powder trough is recovered. During the powder spreading of layers n+1 to m, the powder supply system supplies mixed powder of a second gradient ratio to the lower powder trough. After the powder spreading of layers n+1 to m is completed, the remaining mixed powder of the second gradient ratio in the lower powder trough is recovered. During the powder spreading of layers m+1 to z, the powder supply system supplies mixed powder of a third gradient ratio to the lower powder trough. That is, by supplying powder with different gradient mixing ratios to the powder spreader through the powder supply system, the printed product is printed in a gradient direction along the Z-axis.
[0022] In another embodiment, in step S2, the carbon-based ceramic powder and the pore-forming agent are placed in different powder feeding tanks, and the ratio of carbon-based ceramic powder to pore-forming agent is controlled by controlling the powder feeding speed of each powder feeding tank. In step S3, the powder in each powder trough is mixed in the powder spreading trough and then spread by the powder spreading trough for printing.
[0023] In this embodiment, the powder spreader of the 3D printing equipment is designed with two powder feeding troughs and one powder spreading trough. Powder from each powder feeding trough falls into the powder spreading trough for spreading. By controlling the falling speed of the powder in each powder feeding trough, the mixing ratio of carbon-based ceramic powder and pore-forming agent can be controlled. When the two powders fall into the powder spreading trough, they are mixed there. Therefore, to print in a gradient ratio along the Z-axis, only the powder feeding speed of the carbon-based ceramic powder feeding trough and the pore-forming agent feeding trough needs to be adjusted to achieve different mixing ratios of carbon-based ceramic powder and pore-forming agent. Preferably, the powder supply system is a dual-vibration feeder with a screw for precise powder feeding, achieving an accuracy of ±0.5 vol.
[0024] In another embodiment, the pore-forming agent is polystyrene, and the average particle size of the polystyrene is 5–20 μm. Preferably, the average particle size of the polystyrene is 10 μm.
[0025] In another embodiment, the carbon-based ceramic powder is a carbon-based ceramic powder with an average particle size of 20-50 μm and a purity greater than 99.5%. Preferably, the carbon-based ceramic has an average particle size of 35 μm and a purity of 99.8%.
[0026] In another embodiment, in step S1, the carbon-based ceramic powder is placed in a muffle furnace for pre-oxidation treatment at a temperature of 900–1400°C for a holding time of 60–120 min. Preferably, the temperature is 1300°C and the holding time is 60 min.
[0027] In another embodiment, in step S4, the material is cured in a heat-preserving oven at a temperature of 120–180°C for 60–180 minutes. Preferably, the curing temperature is 160°C and the curing time is 5 hours.
[0028] In another embodiment, in step S4, the degreasing process is as follows: the temperature is increased to 350–750°C at a heating rate of 1–5°C / min, and held for 1–4 hours; then the temperature is increased to 1000–1200°C at a heating rate of 5–10°C / min, and held for 1–2 hours. Preferably, the temperature is increased to 600°C at a rate of 2°C / min, and held for 2 hours.
[0029] In another embodiment, in the degreasing process, the degreasing atmosphere is nitrogen or argon, which completely decomposes and removes the binder and pore-forming agent. Then, the temperature is raised to 1200°C at a rate of 10°C / min and held for 1 hour, so that neck connections (neck diameter > 1 μm) are formed between the carbon-based ceramic particles, and the green body compressive strength reaches 20-50 MPa, thereby forming a carbon-based ceramic preform.
[0030] In another embodiment, in step S5, the vacuum pressure impregnation furnace is evacuated to 1.5-4.0 MPa, heated to 680-720°C at a heating rate of 5-10°C / min, held at that temperature for 5-15 min, and then high-purity nitrogen or argon is introduced at a pressure of 2-5 MPa, and the temperature is held for another 30-90 min.
[0031] Specifically, the carbon-based ceramic preform with a gradient pore structure obtained in step S4 is placed in a vacuum pressure infiltration furnace. The furnace is closed and a vacuum is drawn. Then, the temperature is increased to 550–600°C at a heating rate of 5–10°C / min and held for 10–15 min to homogenize the internal temperature of the preform. The temperature is then increased to 680–720°C, and the induction heater is simultaneously activated to melt the aluminum ingot, thereby filling the entire preform with liquid aluminum. After holding for 5–15 min, high-purity nitrogen or argon gas is introduced into the furnace at a pressure of 2–5 MPa. The temperature is then held for another 30–90 min to achieve the preparation of the gradient aluminum-carbon-based ceramic composite material.
[0032] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0033] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for 3D printing a gradient aluminum-carbon-based ceramic composite material, characterized in that, Includes the following steps: S1, Pretreatment: Pre-oxidation treatment of carbon-based ceramic powder; S2, Gradient ratio powder mixing: The pre-oxidized carbon-based ceramic powder is mixed with the pore-forming agent according to the preset gradient ratio to obtain mixed powders with different ratios. S3, Powder Spreading Printing: Using binder jet 3D printing technology, different gradient ratios of mixed powders are used to spread and print the product in layers according to the requirements of different parts of the product in the Z-axis direction, so as to make a 3D printed product blank with a gradient structure. S4, Post-processing: The 3D printed product green body is sequentially cured, degreased and sintered to obtain a carbon-based ceramic preform with a gradient pore structure; S5, Aluminizing: The carbon-based ceramic preform is placed in a vacuum pressure infiltration furnace for aluminizing treatment to obtain a gradient aluminum-carbon-based ceramic composite material.
2. The 3D printing preparation method according to claim 1, characterized in that, In step S2, the mixed powder is divided into a first gradient ratio, a second gradient ratio, and a third gradient ratio according to the performance requirements of different parts of the product in the Z-axis direction. In step S3, the first gradient ratio of mixed powder is used in the powder coating of layers 1 to n, the second gradient ratio of mixed powder is used in the powder coating of layers n+1 to m, and the third gradient ratio of mixed powder is used in the powder coating of layers m+1 to z, where n, m, and z are positive integers and n <m<z。 3. The 3D printing preparation method according to claim 1, characterized in that, In step S2, the carbon-based ceramic powder and the pore-forming agent are placed in different powder feeding troughs of the powder supply system, and the mixing ratio of carbon-based ceramic powder and pore-forming agent is controlled by controlling the powder feeding speed of each powder feeding trough. In step S3, the powder falling from each powder trough is mixed in the powder spreading trough, and the powder spreading trough is used for powder spreading and printing.
4. The 3D printing preparation method according to claim 1, characterized in that, The pore-forming agent is polystyrene, and the average particle size of the polystyrene is 5-20 μm.
5. The 3D printing preparation method according to claim 1, characterized in that, The carbon-based ceramic powder is a carbon-based ceramic powder with an average particle size of 20-50 μm and a purity greater than 99.5%.
6. The 3D printing preparation method according to claim 1, characterized in that, In step S1, the carbon-based ceramic powder is placed in a muffle furnace for pre-oxidation treatment at a temperature of 900–1400°C and a holding time of 60–120 min.
7. The 3D printing preparation method according to claim 1, characterized in that, In step S4, the curing temperature is 120–180°C and the curing time is 60–180 min.
8. The 3D printing preparation method according to claim 7, characterized in that, In step S4, the degreasing process is as follows: the temperature is increased to 350-750°C at a heating rate of 1-5°C / min, and held for 1-4 hours, with the degreasing atmosphere being nitrogen or argon; then the temperature is increased to 1000-1200°C at a heating rate of 5-10°C / min, and held for 1-2 hours.
9. The 3D printing preparation method according to claim 1, characterized in that, In step S5, the vacuum pressure impregnation furnace is evacuated to 1.5-4.0 MPa, heated to 680-720°C at a heating rate of 5-10°C / min, held at that temperature for 5-15 minutes, and then high-purity nitrogen or argon is introduced at a pressure of 2-5 MPa, and the temperature is held for another 30-90 minutes.
10. The 3D printing preparation method according to claim 1, characterized in that, In step S3, the printing layer thickness is 40–100 μm, the binder saturation is 40%–75%, and the volume fraction of carbon-based ceramic is 20%–50%.